2019
DOI: 10.5334/tohm.471
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Non-Motor Symptoms in Patients with Essential Tremor: Impact on Quality of Life and Age-Related Differences

Abstract: Background: Identifying the clinical phenotypes of non-motor symptoms (NMSs) of essential tremor (ET) among different populations is necessary due to their impact on the quality of life (QoL). This study aimed to investigate the clinical phenotype and impact of NMSs on QoL in Egyptian patients with ET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
5
0
3
Order By: Relevance
“…Our results replicate previous findings of a relatively higher prevalence and severity of anxiety and depression among patients with idiopathic dystonia or ET than in healthy controls ( 6 , 8 , 9 , 11 , 13 16 , 18 20 , 30 ). Although our study did not find a significant difference between the study groups in terms of the frequency of psychiatric disorders diagnosed according to the DSM-IV Axis I ( p = 0.11), psychiatric disorders tended to be more prevalent among patients with IFD than among healthy controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results replicate previous findings of a relatively higher prevalence and severity of anxiety and depression among patients with idiopathic dystonia or ET than in healthy controls ( 6 , 8 , 9 , 11 , 13 16 , 18 20 , 30 ). Although our study did not find a significant difference between the study groups in terms of the frequency of psychiatric disorders diagnosed according to the DSM-IV Axis I ( p = 0.11), psychiatric disorders tended to be more prevalent among patients with IFD than among healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, recent studies have shown that such neuropsychiatric manifestations, including depression, anxiety, and obsessive-compulsive traits, are observed in patients with focal or segmental dystonia (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The recent finding that patients with essential tremor (ET), a common motor characterized dysfunction of the cerebellum and consequent isolated tremor, also present with neuropsychiatric symptoms, may implicate psychiatric manifestations as part of the primary pathophysiology of movement disorders (3,(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…As expected and as noted in prior studies [45][46][47], patients with age at onset of tremor over 65 years had a significantly higher prevalence of cognitive impairment (37.0% vs 13.1%, p = 0.003). Several studies have shown cognitive deficits in ET patients exceeding those of age-matched [3,48,49] and historical controls [50]. A Spanish study found a higher incidence of dementia in ET patients versus controls (7.8% vs 3.9%, unadjusted relative risk = 2.08, p = 0.006) over a mean follow-up of 3.2 years, and ET patients over 65 were twice as likely to develop dementia compared to controls [46].…”
Section: Adj P (Et Plus Vs Et-pd) Medication Historymentioning
confidence: 99%
“…В силу того, что ЭТ чаще всего дебютирует у пациентов пожилого возраста, специалисты считали, что когнитивные нарушения -это не что иное, как характерное для людей в этом возрасте. Однако, в работе Shalash A. et al, где пациенты были разделены на 2 группы: младше 45 лет и старше 45 лет, было выявлено, что при оценке когнитивных нарушений в группе «младше 45 лет» они были выражены значительнее, чем во второй группе, что опровергает теорию корреляции нарушений мыслительных способностей у пациентов с возрастом [17].…”
Section: результаты и обсуждениеunclassified
“…Обоняние и слух. Нарушение слуха у пациентов с ЭТ связывают в некоторых источниках с возможной патологией улитки, а где-то с таким белком, как коннексин, который участвует в ряде патологических состояний у человека, в частности при потере слуха и нейродегенеративных расстройствах [17,18]. При обследовании в домах престарелых 250 пациентов с ЭТ, 127 с БП и 127 здоровых людей было выявлено, что слуховой аппарат был у большинства пациентов с ЭТ, а при выборке из них 74 пациентов при проведении аудиометрии чистым тоном выявлены аномальные значения на высоких частотах, что говорит в пользу наличия у таких пациентов высокочастотной нейросенсорной тугоухости [19].…”
Section: результаты и обсуждениеunclassified